Connecting measurement invasiveness to optimal metrological scenarios - Moreira, Saulo V.; Adesso, Gerardo; Correa, Luis A.; Coudreau, Thomas; Keller, Arne; Milman, Pérola (American Physical Society, 2017)
The connection between the Leggett-Garg inequality and optimal scenarios from the point of view of quantum metrology is investigated for perfect and noisy general dichotomic measurements. In this context, we show that the Fisher information can be expressed in terms of quantum temporal correlations. This connection allows us to associate scenarios with relatively high Fisher information to scenarios in which the Leggett-Garg inequality is violated. We thus demonstrate a qualitative and, to some extent, quantitative link between measurement invasiveness and metrological performance. Finally, we illustrate our results by using a specific model for spin systems.